Єпископ Глухівський та Ніжинський Дамаскін (Цедрик) як один із головних ідеологів ІПЦ в Україні - Шуміло, В. (Сiверянський літопис, 2020)
Метою статті є написання біографії одного з відомих і авторитетних
церковних діячів Чернігівщини періоду 1920–1930-х рр. єпископа Дамаскіна
(Цедрика) як одного з ідеологів та засновників Істинно-Православної (або
інакше – Катакомбної) Церкви в Україні та, зокрема, на Чернігівщині. Методи
дослідження добиралися відповідно до мети та базуються на принципі історизму.
Застосовані методи історіографічного аналізу та синтезу, проблемно-хронологічний, ретроспективний та порівняльний методи. Новизна роботи
полягає в тому, що вперше розглянуто життєвий шлях єпископа Дамаскіна не
тільки як церковного діяча або мученика за віру, який жив в епоху переслідування
православної Церкви в СРСР, але саме як одного з головних ідеологів та
засновників Катакомбної Церкви. Розглянуто розвиток світоглядних поглядів
єпископа Дамаскіна, що призвели його до переконання в тому, що компроміс
православної Церкви з радянською владою в питаннях віри неможливий, а єдиний
шлях для збереження внутрішньої свободи Церкви в умовах знищення в СРСР
свободи віросповідання – перехід на нелегальне становище, – «в катакомби».
Висновки. Єпископ Дамаскін (Цедрик) був ідейно близький до видатних
ієрархів ХХ ст.: митрополитів Антонія (Храповицького), Кирила (Смирнова),
Петра (Полянського), архієпископів Антонія (Абашидзе), Андрія (Ухтомського),
Пахомія (Кедрова) та ін. Він приклав багато зусиль для захисту православної
Церкви від «обновленства», зокрема, в Чернігівській єпархії, одним із перших
православних архієреїв засудив політику митрополита Сергія (Страгородського)
щодо підпорядкування Церкви радянській атеїстичній державі. Саме єпископ Дамаскін зумів налагодити зв'язок з Місцеблюстителем патріаршого престолу митрополитом Петром (Полянським), який перебував на засланні, і з'ясувати позицію першоієрарха щодо «сергіянства». Разом з митрополитом Кирилом (Смирновим) він розробив основи ідеології Катакомбної Церкви в СРСР. The aim of this article is to recount the biography of one of the well-known and authoritative
activists in the Church in the Chernihiv region from the 1920–1930’s, Bishop
Damascene (Tsedrik), who was one of the ideologues and founders of the True Orthodox
(also known as the Catacomb) Church in Ukraine, and specifically in the Chernihiv region.
The research methods used were chosen in relation to the aim and are based on the
principle of historicity. The methods of historiographical analysis and synthesis were
used, as well as methods dealing with the problem of chronology and of retrospection,
and comparative methodology. The originality of the work lies in the fact that for the first
time the life of Bishop Damascene is examined not only as that of a minister in the Church
and a martyr for his faith that lived in the period of repression of the Orthodox Church in
the USSR, but also as that of one of the main ideologues and founders of the Catacomb
Church. The development of Bishop Damascene’s understanding of the world around
him, which lead him to the conclusion that compromise between the Orthodox Church
and the soviet government in matters of faith was impossible, and the conviction that
the only way to preserve the inner freedom of the Church in the conditions of the USSR’s
destruction of the freedom of religion was to function outside the law, in “the catacombs|
is fully examined.
Conclusions. Ideologically Bishop Damascene was similar to other outstanding hierarchs
of the XX century: Metropolitans Anthony (Khrapovitsky), Kirill (Smirnov), Peter
(Polyansky), Archbishops Anthony (Abashidze), Andrew (Ukhtomsky), Pachomius (Kedrov),
and others. He worked hard to defend the Orthodox Church against the “renovationists
», specifically in the Chernihiv diocese. He was one of the first Orthodox hierarchs
to condemn the politics of Metropolitan Sergius (Stragorodsky), which subjugated the
Church to the atheist soviet government. Bishop Damascene was the one who managed
to contact the locum tenens of the Patriarchal seat, Metropolitan Peer (Polyansky), who
was in exile at the time, to find out what he thought of “sergianism». Together with Metropolitan
Kirill (Smirnov) he laid down the foundation of the ideology of the Catacomb
Church in the USSR.